2002
DOI: 10.1021/ma011465s
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Ultrathin Hydrogels Prepared by Sequential Chemical Reactions

Abstract: Thermoresponsive ultrathin hydrogels were prepared by the sequential chemical reaction of poly(vinylamine-co-N-vinylisobutyramide) [poly(VAm-co-NVIBA)] and poly(acrylic acid) (polyAAc) on a gold surface. The carboxyl group of polyAAc was activated by 1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide hydrochloride (EDC) for the reaction with the amino group of poly(VAm-co-NVIBA) to yield the amide linkage. This stepwise assembly was analyzed quantitatively by a quartz crystal microbalance (QCM), which revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
90
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 33 publications
0
90
0
Order By: Relevance
“…These swelling ratios were similar to those reported for ultrathin hydrogels previously prepared using copolymers of N-vinylalkylamides. 5,6 Even in the absence of EDC, the film obtained swelled slightly with water molecules, possibly due to the presence of monomer units that did not related to the noncovalent interactions between the polymers. The percent incremental increase in assembly thickness was dependent on the amount of EDC, and increased with the amount of EDC.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…These swelling ratios were similar to those reported for ultrathin hydrogels previously prepared using copolymers of N-vinylalkylamides. 5,6 Even in the absence of EDC, the film obtained swelled slightly with water molecules, possibly due to the presence of monomer units that did not related to the noncovalent interactions between the polymers. The percent incremental increase in assembly thickness was dependent on the amount of EDC, and increased with the amount of EDC.…”
Section: Resultsmentioning
confidence: 98%
“…5,6 It was demonstrated that copolymers of acrylamides are also available as constituents in the formation of ultrathin hydrogels. Thickness analysis in air and water revealed the unique water swelling properties of the resulting ultrathin hydrogels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations